The Country of Origin Principle and the Applicable Law for Obligations Related to the Benefit of Information Society Services - Kotkowski, Mateusz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The article takes all of the abovementioned legacy of European Union Law into consideration while analysing them in depth through the prism of the principle in question and via careful comparisons of each of them as well. Particular attention is paid to the following issues, namely: the legal nature of the principle in question, its treaty sources, its scope of application, the principle in question in the light of the abovementioned directives – namely the Directive on audiovisual media services and the Directive on electronic commerce; and finally – relationships between provisions of the two aforementioned directives in the context of audiovisual media services on demand. While working on the text, all of the mentioned parts of the main subject turned out to be important enough to put them into separated sections of the text with their own individual headings. In the meantime, several interesting subject-related sentences by the European Court of Justice were also taken into account for a broadened pool of reference. To sum it all up: ultimately, the principle in question and its potential influence on the practical functioning of the European Union’s law and economy has been considered thoroughly.